Students’ Perception of Learning Strategy Using Grammar Translation Method in Reading Skill at SMA 2 PGRI Palembang - Shinta Agustin; Yuspar Uzer; Ferri Hidayad (LPPM Universitas Bumigora Mataram, 2022)
AbstractPeople communicate each other by using language. One of the international language used in countriesthrough the world, including Indonesia, English has become one of the subjects taught widely in thisarchipelago country. In Indonesia English was the first foreign language thought in official learning,starting from elementary schools until as s compulsory subject in high schools and universities. Thepurpose of this study was to determine and describe students’ perceptions of learning strategies using theGrammar Translation Method in reading skills. The research method used in this research was usedqualitative methods. The subjects of this study were 34 students of 10th grade science class and twoEnglish teachers at SMA 2 PGRI Palembang. The results of this study indicate that some students alreadyknow what is learning strategy and this method in learning, especially in using the grammar translationmethod and some students feels motivated in using this method. In addition, teachers also understandwhat is learning strategies and they also used this method on the learning and teaching process because byusing a strategy material can be conveyed properly and made learning process more structured, easy tounderstand. Using this method also can help achieve the language targets what students want to achieve.